2018
DOI: 10.1002/ejoc.201800183
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Preliminary Biological Evaluation of GlcNAc‐6P Analogues for the Modulation of Phosphoacetylglucosamine Mutase 1 (AGM1/PGM3)

Abstract: A library of GlcNAc 6‐ or 1‐phosphate analogues was designed, and each compound was evaluated computationally through docking studies for its binding affinity to AGM1/PGM3. The compounds with the highest binding affinity, as ranked through a docking score, were synthesised and screened for their ability to inhibit the production of UDP‐GlcNAc. A glycofused oxazoline analogue showed good inhibition, and gave significant results in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…To further detail the role of the KRAS status in the dependence of the PDAC cells on HBP and N -glycosylation processes, we took advantage of an HBP inhibitor previously generated by our group, named FR054 [ 13 ], which is able to inhibit the HBP enzyme PGM3 causing a reduction in the HBP flux and consequently a significant attenuation of both protein N - and O -glycosylations [ 14 , 15 ]. MIA PaCa-2, PANC-1 and BxPC-3 cell lines were treated for 48 h with different concentrations of FR054 and then the cell viability and death were quantified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further detail the role of the KRAS status in the dependence of the PDAC cells on HBP and N -glycosylation processes, we took advantage of an HBP inhibitor previously generated by our group, named FR054 [ 13 ], which is able to inhibit the HBP enzyme PGM3 causing a reduction in the HBP flux and consequently a significant attenuation of both protein N - and O -glycosylations [ 14 , 15 ]. MIA PaCa-2, PANC-1 and BxPC-3 cell lines were treated for 48 h with different concentrations of FR054 and then the cell viability and death were quantified.…”
Section: Resultsmentioning
confidence: 99%
“…Oxamate, 2-deoxyglucose (2-DG), and mannose were purchased from Sigma-Aldrich (Merck Life Science, Milan, Italy). FR054 was synthesized either by our laboratories or by WuXi AppTec Co., Ltd. (Tianjin, China) [ 13 , 14 ]. The RAS inhibitor BI-2852 was requested and obtained from Boehringer Ingelheim (Ingelheim am Rhein, Germany) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the recently developed FR054 showed inhibitory activity against PGM3 (Table ). , GAL-012 and the UTP a , b -methylenebisphosphonate analogue (meUTP) were synthesized as inhibitors to eukaryotic UAP1 (Table ). , Due to the critical role in the regulation of UDP-GlcNAc, HBP-targeting drugs may have attractive utility as therapeutics (which will be discussed in the following sections).…”
Section: Characterization Of Hbp and Udp-glcnacmentioning
confidence: 99%
“…PGM3, the third enzyme in the HBP, represents another target for cancer therapy. FR054 (Table ), a specific inhibitor to PGM3, has been designed and used in several preclinical studies recently. ,, One study revealed FR054 efficiently induces an early decrease of intracellular UDP-GlcNAc and hence diminishes O-GlcNAc and N-glycosylation, leading to reduced breast cancer cell adhesion and migration . Moreover, FR054 represses tumor growth in a xenograft mice mode.…”
Section: Biomedical Applicationsmentioning
confidence: 99%